The influence of the fineness of metakaolin on the properties of self-compacting underwater concrete - Grzeszczyk, Stefania; Jurowski, Krystian (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the research results of the influence of metakaolin of different fineness that is applied as a microfiller (20% of the cement mass) on the properties of self-compacting underwater concrete. It is demonstrated that the metakaolin with higher fineness improves the efficiency of antiwashout admixture and superplasticizer in concrete mixture. It was revealed that the higher resistance to washout of cement paste from the concrete mixture and higher flowability in comparison to the mixture containing metakaolin with lower content of fine fraction (below 10μm). In addition, the positive effect of the higher fineness of metakaolin on the compressive strength and freeze thaw scaling resistance was proven in the self-compacting underwater concrete.